Preparation method and application of S and N co-doped small-nano-size high-entropy intermetallic compound

Through a preparation method of S,N co-doped small nanometer-sized high-entropy intermetallic compounds, the problem of slow kinetics of cathode oxygen reduction reaction in fuel cells is solved, and a high-activity and high-stability catalyst is achieved, and simplified synthesis Steps and reduce costs.

CN119447329AActive Publication Date: 2025-02-14TONGJI UNIV +1

Patent Information

Application Number
CN202411601467.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The oxygen reduction reaction kinetics of the cathode of the existing proton exchange membrane fuel cell are slow, and the low reserves, high prices and poor cycle stability of the catalyst precious metal platinum limit the large-scale commercial application of fuel cells.

Method used

Using a preparation method for a small nanometer-sized high-entropy intermetallic compound co-doped S,N, by stirring noble metal salts, transition metal salts, sulfur sources and nitrogen sources with carbon support in an organic solvent, ultrasonic treatment, and then in Dried in a vacuum oven and annealed at high temperature in a reducing atmosphere to prepare a small nanometer-sized high-entropy intermetallic compound catalyst co-doped S,N.

Benefits of technology

This method simplifies the synthesis steps of the catalyst, reduces costs, improves the activity and stability of the catalyst, and especially shows excellent performance in oxygen reduction catalysis, which can significantly improve the performance and stability of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447329A_ABST
    Figure CN119447329A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and an application of an S and N co-doped small-nano-size high-entropy intermetallic compound. 2, 2 '-bithiophene is simultaneously used as a metal ligand and a sulfur source to be applied to synthesis of the high-entropy intermetallic compound, and sulfur atoms in the substance can form a complex with metal ions, so that a metal precursor can be uniformly and firmly distributed on the surface of a commercial carbon carrier, and formation of the high-entropy intermetallic compound in the subsequent annealing process is facilitated; the S and N co-doped high-entropy alloy intermetallic compound catalyst synthesized by the invention has excellent electrochemical performance in a fuel cell, and particularly has remarkable performance in the aspect of stability; wherein the mass activity of the S and N co-doped high-entropy alloy intermetallic compound PtCuNiCoFe / C-SN (PCNCF-SN) catalyst under the condition of 0.9 V (vs.RHE) reaches 2.7 A * mg <-1 > Pt, which is more than 12.3 times of that of commercial Pt / C; and in the aspect of stability, the mass activity can still be kept at 65% or above after 100000 circles of accelerated durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of fuel cell catalysts, and in particular relates to a catalyst used for a cathode of a proton exchange membrane fuel cell, and specifically relates to a preparation method for synthesizing a small nano-sized high entropy intermetallic compound on a carbon carrier and its application in a fuel cell. Background Art

[0002] Hydrogen energy is a green, efficient and perfect energy source, and proton exchange membrane fuel cell is one of the efficient means of utilizing hydrogen energy. Different from traditional internal combustion engine technology, its method of directly converting chemical energy into electrical energy breaks through the limitations of the Carnot cycle, thereby greatly improving the energy conversion efficiency. Due to its high efficiency, zero product pollution, and rich application scenarios, it has attracted much attention in the field of energy research.

[0003] However, the oxygen reduction reaction at the cathode of proton exchange membrane fuel cells still faces the problem of slow kinetics. Today's fuel cell catalysts are still mainly based on the precious metal platinum. Due to the low reserves and high price of platinum and poor cycle stability, the large-scale commercial application of fuel cells is greatly limited. Although a large number of catalysts have been reported, they have certain problems in one or more aspects such as the difficulty of synthesis, activity and stability, and cannot take into account simple synthesis and efficient performance. Therefore, it is of great significance to develop a synthesis method with simple synthesis, strong universality and low cost to synthesize new catalysts with high activity and high stability.

[0004] Due to their high entropy effect and ordered structure, high entropy intermetallic compounds have excellent performance in terms of activity and stability, especially in terms of stability. However, their synthesis conditions are relatively harsh, and they usually face a series of problems brought about by the high-temperature annealing step, such as the aggregation of catalyst particles, which has the most serious impact on performance. In order to solve this key problem, carbon carriers or templates with special confinement effects are usually constructed to inhibit the aggregation and growth of particles. However, this step undoubtedly increases the difficulty and cost of synthesis, and is not conducive to the large-scale production and application of such catalysts.

[0005] In summary, in order to solve these problems, the present invention proposes a synthesis method with simple steps, strong universality and low cost to efficiently synthesize high-entropy intermetallic compounds. The synthesized catalyst shows excellent activity and stability in oxygen reduction catalysis. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing S, N co-doped small nano-sized high entropy intermetallic compounds.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a S, N co-doped small nano-sized high entropy intermetallic compound, comprising:

[0010] A noble metal salt and a transition metal salt, a sulfur source and a nitrogen source are added to an organic solvent, and the mixture is stirred at room temperature. A carbon carrier is added and stirred at room temperature to obtain a mixture, and the mixture is ultrasonically treated to form a uniform mixture A.

[0011] The mixture A was stirred at room temperature, and the organic solvent was evaporated by heating to form a black viscous slurry B, which was transferred to a vacuum oven for drying to obtain an intermediate product;

[0012] The intermediate product is subjected to high temperature annealing treatment in a reducing atmosphere to obtain a S, N co-doped small nano-sized high entropy intermetallic compound;

[0013] Wherein, the sulfur source includes 2,2'-bithiophene, and the organic solvent includes acetone;

[0014] The S, N co-doped small nano-sized high entropy intermetallic compound comprises a carbon carrier containing S and N co-doped heteroatom sites, metal single atom sites, and a high entropy intermetallic compound supported on a carbon substrate;

[0015] The S, N co-doped small nano-sized high entropy intermetallic compound comprises high entropy intermetallic compound particles composed of more than 5 metal elements;

[0016] The particle size of the S, N co-doped small nano-sized high entropy intermetallic compound particles is 2 to 5 nm.

[0017] As a preferred embodiment of the preparation method of the present invention, the noble metal salt comprises at least one of a platinum salt, an iridium salt and a palladium salt;

[0018] Among them, the platinum salt is platinum acetylacetonate, the iridium salt is iridium acetylacetonate, and the palladium salt is palladium acetylacetonate.

[0019] As a preferred embodiment of the preparation method of the present invention, the transition metal salt is a combination of at least three of copper salt, nickel salt, cobalt salt, iron salt, manganese salt and chromium salt;

[0020] Among them, the copper salt is copper acetylacetonate, the nickel salt is nickel acetylacetonate, the cobalt salt is cobalt acetylacetonate, the iron salt is iron acetylacetonate, the manganese salt is manganese acetylacetonate, and the chromium salt is chromium acetylacetonate.

[0021] As a preferred embodiment of the preparation method of the present invention, the nitrogen source is any one of melamine, pipemidic acid, aminoantipyrine, triaminopyrazole and pyridine.

[0022] As a preferred embodiment of the preparation method of the present invention, the carbon carrier is at least one of carbon black, carbon nanotubes and Ketjen black.

[0023] As a preferred embodiment of the preparation method of the present invention, the molar ratio of the noble metal salt to the transition metal salt is (6-8):5; the mass ratio of the noble metal salt to the carbon carrier is (3-4):10; and the mass ratio of the sulfur source, nitrogen source and carbon carrier is 1-2:1-2:1-12.

[0024] As a preferred embodiment of the preparation method of the present invention, the carbon carrier is added and stirred at room temperature to obtain a mixture, wherein the stirring time is 30 to 60 minutes; the mixture is ultrasonically treated to form a uniform mixture A, wherein the ultrasonic time is 1 to 4 hours; the organic solvent is heated to evaporate, wherein the temperature of the evaporating solvent is 70°C and the action time is 0.5 to 1 hour; B is transferred to a vacuum oven for drying, wherein the drying temperature is 60°C and the time is 12 to 24 hours.

[0025] As a preferred embodiment of the preparation method of the present invention, the high temperature annealing atmosphere is 10% H2 / Ar, the annealing heating rate is 3-5°C / min, the annealing temperature is 800-1000°C, and the annealing time is 2-4h.

[0026] Another object of the present invention is to overcome the deficiencies in the prior art and provide a S, N co-doped small nano-sized high entropy intermetallic compound.

[0027] Another object of the present invention is to overcome the deficiencies in the prior art and provide a S, N co-doped small nano-sized high entropy intermetallic compound for use in the cathode oxygen reduction reaction of a proton exchange membrane fuel cell.

[0028] Beneficial effects of the present invention:

[0029] (1) The present invention is the first to use 2,2'-bithiophene as both a metal ligand and a sulfur source in the synthesis of high-entropy metal compounds. Since the sulfur atoms in the substance can form complexes with metal ions, the metal precursor can be evenly and firmly distributed on the surface of the commercial carbon carrier, so as to facilitate the formation of high-entropy metal compounds in the subsequent annealing process. At the same time, the anchoring effect of the S element can not only inhibit the growth of catalyst particles during the annealing process, but also directly use commercial carbon carriers without the need to prepare special carbon carriers or pre-treat the carbon carriers, which greatly reduces costs and simplifies steps.

[0030] (2) The acetone solvent used in the present invention has the characteristics of low boiling point and easy recycling, which also makes it possible to further reduce the cost; in addition, the introduction of multiple transition metals and non-metallic elements into the high entropy metal intermetallic compound catalyst greatly reduces the amount of precious metal platinum, further reducing the cost of the catalyst; the synthesis method synthesizes S, N co-doped high entropy metal intermetallic compounds with small nanometer size in one step through a simple impregnation method and subsequent high temperature annealing; from the perspective of materials, not only the synthesis of high entropy metal intermetallic compound catalyst particles is achieved in one step, but also the co-doping of non-metallic elements N, S and the formation of single atomic sites of MN, MS are achieved on the carbon substrate at the same time; from the perspective of the synthesis method, it is not only simple and easy to operate, low cost, high repeatability, but also the synthesized material has high purity and crystallinity.

[0031] (3) The synthesis method proposed in the present invention has universality and extensibility for a variety of metal elements. It stands to reason that platinum group metals (PGMs) with similar chemical properties to Pt, such as Ir, Pd, Ru, and Rh, are easy to mix randomly at the same crystallographic site, while elements in 4d transition metals, such as copper, nickel, cobalt, iron, chromium, and manganese, are metal elements with atomic radii and electronegativity significantly different from those of platinum group metals. Therefore, after successfully synthesizing a high-entropy metal compound containing five elements of platinum, copper, nickel, cobalt, and iron, it is inferred that a series of high-entropy metal compounds composed of platinum group elements and elements in 4d transition metals can be prepared by the synthesis method of the present invention, and this has also been verified in the successful synthesis of an eight-membered ultra-high-entropy metal compound after adding three elements of iridium, manganese, and chromium.

[0032] (4) The S, N co-doped high entropy alloy intermetallic compound catalyst synthesized by the present invention has excellent electrochemical performance in fuel cells, especially in terms of stability. Among them, the mass activity of the S, N co-doped high entropy alloy intermetallic compound PtCuNiCoFe / C-SN (PCNCF-SN) catalyst at 0.9V (vs.RHE) reached 2.7A / mg Pt, which is 12.3 times that of commercial Pt / C. In terms of stability, after 100,000 cycles of accelerated endurance, the mass activity can still be maintained at more than 65%, which is a great improvement compared with commercial Pt / C catalysts. In addition, in the hydrogen-air fuel cell constructed with this catalyst as the cathode, the peak power density reaches 0.66W / cm 2 ; After 20,000 cycles of accelerated endurance cycling, the peak power density retention rate reached more than 75%, indicating the excellent stability of the catalyst in the membrane electrode; The peak power density of the low S, N content co-doped high entropy alloy metal compound PtCuNiCoFe / C-Low-SN (PCNCF-LSN) catalyst in the membrane electrode reached 0.93W / cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0034] Figure 1 This is a transmission electron microscope (TEM) image of the catalyst PCNCF-SN prepared in Example 1.

[0035] Figure 2 This is a statistical distribution diagram of the particle size of the catalyst PCNCF-SN prepared in Example 1.

[0036] Figure 3 It is the X-ray diffraction pattern of the catalyst PCNCF-SN prepared in Example 1 and commercial Pt / C.

[0037] Figure 4 This is the X-ray photoelectron spectrum (XPS) of nitrogen (a) and sulfur (b) elements in the catalyst PCNCF-SN prepared in Example 1.

[0038] Figure 5 It is a polarization curve diagram of the catalyst PCNCF-SN prepared in Example 1 and the commercial Pt / C catalyst when catalyzing oxygen reduction reaction in 0.1 mol per mole perchloric acid solution.

[0039] Figure 6 This is a polarization curve diagram of the catalyst PCNCF-SN prepared in Example 1 after accelerated durability test (ADT).

[0040] Figure 7 It is a bar graph of the mass activity change of the catalyst PCNCF-SN prepared in Example 1 at the initial, 40,000, 70,000 and 100,000 cycles.

[0041] Figure 8 The polarization curve and power density diagram of a hydrogen-air fuel cell constructed with the material obtained in Example 1 as the cathode and commercial Pt / C (20% TKK) as the anode before and after the accelerated durability test (AST).

[0042] Fig. 9 The polarization curves and power density diagrams of a hydrogen-air fuel cell constructed with the material obtained in Example 2 as the cathode material and commercial Pt / C (20% TKK) as the anode after short-time activation (4h) and long-time activation (14h).

[0043] Fig.10 It is the X-ray diffraction pattern of the catalyst PtIrCuNiCoFeCrMn / C-SN (abbreviated as PICNCFCM-SN) and Pt / C prepared in Example 3.

[0044] Fig.11 This is the elemental energy spectrum of the catalyst PtIrCuNiCoFeCrMn / C-SN (abbreviated as PICNCFCM-SN) prepared in Example 3 obtained by scanning electron microscope-X-ray spectrometer (SEM-EDX).

[0045] Fig.12 This is a transmission electron microscope image of PtCuNiCoFe / C (abbreviated as PCNCF) prepared in Comparative Example 1.

[0046] Fig.13 It is the X-ray diffraction pattern of PtCuNiCoFe / C (abbreviated as PCNCF) prepared in Comparative Example 1 and commercial Pt / C.

[0047] Fig.14 It is a comparison diagram of polarization curves of PtCuNiCoFe / C (abbreviated as PCNCF) prepared in Comparative Example 1 and catalyst PCNCF-SN obtained in Example 1 when catalyzing oxygen reduction reaction in 0.1 mol per mole perchloric acid solution.

[0048] Fig.15 These are the X-ray diffraction patterns of PCNCF-S obtained in Comparative Example 2, PCNCF-SN prepared in Example 1, and PCNCF obtained in Comparative Example 1.

[0049] Fig.16 It is a comparison diagram of polarization curves of PCNCF-S obtained in Comparative Example 2 and PCNCF-SN prepared in Example 1 when catalyzing oxygen reduction reaction in 0.1 mol per mole perchloric acid solution.

[0050] Fig.17These are X-ray diffraction patterns of PCNCF-piperidic acid, PCNCF-thiourea-piperidic acid, PCNCF-1,2-dimethylimidazole-piperidic acid prepared in Comparative Example 3, PCNCF-methanol prepared in Comparative Example 4, and PCNCF-SN prepared in Example 1.

[0051] Fig.18 Polarization curves of PCNCF-piperidic acid, PCNCF-thiourea-piperidic acid, PCNCF-1,2-dimethylimidazole-piperidic acid prepared in Comparative Example 3, PCNCF-methanol prepared in Comparative Example 4, and PCNCF-SN prepared in Example 1 when catalyzing oxygen reduction reaction in 0.1 mol per mole perchloric acid solution. DETAILED DESCRIPTION

[0052] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0053] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0054] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0055] The specific information of the raw materials used in the examples and comparative examples of the present invention are as follows:

[0056] Metal precursor materials: platinum acetylacetonate (97%), iridium acetylacetonate (97%), copper acetylacetonate (97%), nickel acetylacetonate (95%), cobalt acetylacetonate (97%), iron acetylacetonate (98%), chromium acetylacetonate (98%), manganese acetylacetonate (97%); iridium acetylacetonate (97%) was from Sigma-Aldrich, and the other reagents were from McLean.

[0057] Non-metallic sources: 2,2'-bithiophene (98%, Aladdin), pipemidic acid (98%, Aladdin), thiourea (99%, McLean), 1,2-dimethylimidazole (99%, McLean).

[0058] Carbon material: Ketjen black (ECP-600JD, Kelude).

[0059] Solvents: acetone (analytical grade 500 mL, Sinopharm Shanghai Testing), methanol (gradient grade M6600-4L, Inochem).

[0060] Materials used for electrochemical testing in the embodiments of the present invention: deionized water (18.2 MΩ*cm@25°C), perchloric acid (superior pure 500 mL 74%-76%, Sinopharm Shanghai test), Nafion solution (D5205% 10 mL, Suzhou Shengernuo Technology Co., Ltd.), anhydrous ethanol (analytical pure 500 mL, Sinopharm Shanghai test).

[0061] Example 1

[0062] This embodiment provides a method for preparing a S, N co-doped small nano-sized high entropy intermetallic compound catalyst PtCuNiCoFe / C-SN (abbreviated as PCNCF-SN), comprising the following steps:

[0063] (1) 9.5 mg of platinum acetylacetonate, 5.4 mg of copper acetylacetonate, 5.4 mg of nickel acetylacetonate, 5.3 mg of cobalt acetylacetonate, 7.2 mg of iron acetylacetonate, 20 mg of 2,2'-bithiophene and 20 mg of pipemidic acid were added to a reaction vessel;

[0064] Then, 20 ml of acetone was added to form a uniform orange-yellow solution (containing a small amount of undissolved pipemidic acid); the solution was stirred at a speed of 500 r / min, and 50 mg of Ketjen Black was gradually added during the stirring process; after a black suspension was formed, the stirring was continued at a speed of 500 r / min for 30 min, and then the black suspension was ultrasonically treated for 1 h;

[0065] The black suspension was transferred to a beaker and the temperature was raised to 70°C while stirring to evaporate most of the acetone to obtain a black slurry; the black slurry was transferred to a vacuum oven at 60°C and dried for 12 hours;

[0066] (2) transferring the sample obtained in step (1) into a crucible, heating the sample to 800° C. at a rate of 3° C. / min in 10% H2-Ar (hydrogen volume ratio is 10%) for 4 h, and naturally cooling the sample to room temperature to obtain S, N co-doped PtCuNiCoFe / C-SN (PCNCF-SN) high entropy intermetallic compound nanocatalyst;

[0067] Figure 1 is a transmission electron microscope image of the PCNCF-SN catalyst material prepared in Example 1; Figure 2 is the particle size distribution frequency histogram of PCNCF-SN catalyst. Figure 1 and Figure 2 It can be seen that the PCNCF-SN catalyst particles prepared in Example 1 are uniformly dispersed on the carbon support, and the average particle size is 3.8 nm.

[0068] Figure 3 This is the X-ray diffraction pattern of the PCNCF-SN catalyst material prepared in Example 1; it can be seen from the figure that, similar to Pt / C, PCNCF-SN also forms an FCC single-phase structure dominated by the (111) crystal plane, without segregation of other transition metal phases. In addition, each diffraction peak shifts to a higher angle, indicating that the doping of transition metals leads to a certain lattice contraction, and the appearance of ordered diffraction peaks (stars) indicates the formation of high entropy metal compounds.

[0069] Table 1 shows the mass fractions of various metal elements in the PCNCF-SN catalyst material prepared in Example 1 measured by inductively coupled plasma-atomic emission spectroscopy;

[0070] Element Type Pt Cu Ni Co Fe Quality score 5.5% 1.9% 1.5% 1.6% 1.1%

[0071] It can be seen from this that the total amount of metal is about 11% by mass, platinum accounts for about half of the total, and other metal elements are close to 1-2%.

[0072] Figure 4 It is the X-ray photoelectron spectrum of sulfur (a) and nitrogen (b) elements in the PCNCF-SN catalyst material prepared in Example 1; it can be observed that metal nitrogen bonds (MN), metal sulfur bonds (MS) and N, S heteroatom sites are formed on the carbon substrate, which are beneficial to anchoring the synthesized high entropy metal intermetallic compound catalyst particles on the carbon support.

[0073] 20 mg of the PCNCF-SN catalyst prepared in Example 1 was mixed with 990 μL of anhydrous ethanol and 10 μL of Nafion solution, and the mixture was ultrasonically treated for 1 h to obtain a uniformly mixed black ink.

[0074] The catalyst ink was drawn with a pipette and coated on a glassy carbon (GC) electrode with a diameter of 5 mm. This electrode was used as the working electrode, and a three-electrode test system was formed with a platinum wire electrode as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a 0.1 M perchloric acid solution as the electrolyte. The catalyst was tested under this system, and oxygen was continuously introduced. Cyclic voltammetry (CV) scanning was performed to activate the catalyst while maintaining sufficient dissolved oxygen in the electrolyte. The scanning range was -0.05 V to 0.95 V, and the scanning speed was 200 mV s -1 After activation, a linear sweep voltammetry (LSV) test was performed with a scan range of -0.05V to 1.05V and a scan rate of 10mV s -1 , and obtain the polarization curve of the catalyst.

[0075] The specific steps of the accelerated durability test (ADT) of the PCNCF-SN catalyst are as follows: 100,000 cycles of CV scanning were performed with a scanning range of 0.4 V to 0.9 V (relative to the reversible hydrogen electrode) and a scanning rate of 200 mV s -1 , LSV tests were performed at 40000, 70000 and 100000 cycles respectively to obtain the polarization curves after accelerated durability.

[0076] Figure 5 Polarization curve of the PCNCF-SN catalyst material prepared in Example 1 in a half-cell; it can be found that the half-wave potential of the material prepared by this method is increased by 60 mV compared with the commercial Pt / C catalyst, which means that the activity of the catalyst has been greatly improved.

[0077] Figure 6 is a polarization curve diagram of the PCNCF-SN catalyst material prepared in Example 1 after accelerated durability testing;

[0078] Figure 7 Is Figure 6 The calculated catalyst mass activity decay bar graph; the current density at 0.9V and 0.4V in the LSV curve was taken, the kinetic current density was calculated by the Koutecky–Levich equation, and the mass activity (MA) of the catalyst was obtained by normalizing the mass of the precious metal. From the above two figures, it can be seen that after 100,000 cycles, the mass activity only lost 34.2%, and the attenuation of the polarization curve was not obvious, which means that the material prepared by this method has excellent stability.

[0079] Figure 8 The polarization curve and power density diagram of the hydrogen-air fuel cell constructed with the material obtained in Example 1 as the cathode and commercial Pt / C (20% TKK) as the anode before and after the accelerated durability test (AST); it can be seen from the figure that the initial peak power density reaches 0.66W / cm 2 ; After 20,000 cycles of accelerated endurance cycling, the peak power density retention rate is still above 75%, indicating the excellent stability of the catalyst in the membrane electrode; It is worth mentioning that the current density in the high voltage region of the polarization curve after 20,000 cycles is higher than that of the polarization curve before the cycle (i.e., the hollow triangle curve is above the green hollow circle), which indicates that the catalyst activity is slightly improved after the cycle; However, when the voltage drops below 0.6 volts, the corresponding current density drops faster, which indicates that in the high current region, mass transfer obstruction is the main reason for the decline in catalyst activity and performance after cycling.

[0080] Example 2

[0081] This embodiment provides a method for preparing a small nano-sized high entropy intermetallic compound catalyst PtCuNiCoFe / C-Low-SN (abbreviated as PCNCF-LSN) with low S and N content, which is a variation of Example 1. The variation is that the mass ratio of 2,2'-bithiophene and pipemidic acid to the carbon carrier is adjusted to 1:10, and the other steps are the same as Example 1.

[0082] Fig. 9 The polarization curves and power density diagrams of the hydrogen-air fuel cell constructed with the material obtained in Example 2 as the cathode and commercial Pt / C (20% TKK) as the anode after short-time activation (4h) and long-time activation (14h) are shown; it can be found that the catalyst with changed S and N contents has better performance in the membrane electrode, and the peak power density reaches 0.75W / cm after 4h of activation. 2 After 14 hours of activation, the performance was further improved to 0.93W / cm 2 , and thus found that regulating the content of non-metallic elements can further improve the performance of catalysts in membrane electrodes.

[0083] Example 3

[0084] This embodiment provides a method for preparing a S, N co-doped small nano-sized high entropy intermetallic compound catalyst PtIrCuNiCoFeCrMn / C-SN (abbreviated as PICNCFCM-SN), which is a variation of Embodiment 1. The variation is that the components of precious metals and transition metals are added to prepare an ultra-high entropy intermetallic compound composed of eight metal elements, which specifically includes the following steps:

[0085] (1) 9.5 mg of platinum acetylacetonate, 11.2 mg of iridium acetylacetonate, 5.4 mg of copper acetylacetonate, 5.4 mg of nickel acetylacetonate, 5.3 mg of cobalt acetylacetonate, 7.2 mg of iron acetylacetonate, 54 mg of chromium acetylacetonate, 56 mg of manganese acetylacetonate, 20 mg of 2,2'-bithiophene and 20 mg of pipemidic acid were added to a reaction vessel; 20 ml of acetone was then added to form a uniform orange-yellow solution (containing a small amount of undissolved pipemidic acid); the solution was stirred at a speed of 500 r / min, and 50 mg of Ketjen black was gradually added during the stirring process; after a black suspension was formed, the stirring was continued at a speed of 500 r / min for 30 min, and then the black suspension was ultrasonically treated for 1 h; the black suspension was transferred to a beaker, and the temperature was raised to 70°C while stirring, in order to evaporate most of the acetone to obtain a black slurry; the black slurry was transferred to a vacuum oven at 60°C and dried for 12 h;

[0086] The sample obtained in (1) was transferred into a crucible, heated to 1000°C at a rate of 3°C / min in 10% H2-Ar for 4 h, and naturally cooled to room temperature to obtain S, N co-doped PtIrCuNiCoFeCrMn / C-SN high entropy intermetallic compound nanocatalyst;

[0087] Fig.10 It is the X-ray diffraction pattern of the PtIrCuNiCoFeCrMn-SN catalyst material prepared in Example 2; ordered diffraction peaks can be observed in the figure, and there are no impurity peaks of metal segregation, indicating that a high entropy intermetallic compound structure is formed.

[0088]

[0089] Fig.11 and Table 2: The energy spectrum and quantitative data of each element obtained by scanning electron microscope-X-ray spectrometer (SEM-EDX) of the catalyst PICNC FCM-SN prepared in Example 2;

[0090] Table 2 Element contents of the catalyst PICNC FCM-SN prepared in Example 2 obtained by scanning electron microscope-X-ray spectrometer (SEM-EDX)

[0091] It can be seen from this data that the ultra-high entropy alloy was successfully synthesized, and the normalized mass proportion of each metal element is above 5%, which meets the definition of high entropy alloy.

[0092] comprehensive Fig.10 , Fig.11 and Table 2, indicating that segregation-free ultra-high entropy alloys were synthesized by this method, demonstrating the excellence of this method in the synthesis of high-entropy alloy catalysts.

[0093] Comparative Example 1

[0094] This comparative example is intended to verify that the introduction of S, N-containing organic compound raw materials (such as 2,2'-bithiophene and pipemidic acid) in the preparation method of the present invention has a crucial influence on the successful preparation and performance of the final catalyst.

[0095] The catalyst PtCuNiCoFe / C (abbreviated as PCNCF) in this comparative example was prepared by the same steps as in Example 1, except that 2,2'-bithiophene and pipemidic acid were not added, and other conditions were the same as in Example 1.

[0096] Fig.12 This is a transmission electron microscope image of PCNCF prepared in comparative example 1; it can be clearly found from the image that the particle size of the synthesized material is relatively large and the aggregation phenomenon is obvious, indicating that the introduction of 2,2'-bithiophene and pipemidic acid plays a crucial role in the success of the synthesis.

[0097] Fig.13 It is an X-ray diffraction diagram of PCNCF prepared in Comparative Example 1; it can be seen from the figure that the position of the diffraction peak has changed, indicating that there is no introduction of non-metallic elements, the compression of the lattice is more obvious, and the diffraction peak is narrowed, which indicates that the particle size of the synthesized catalyst is larger, which is different from Fig.10 The results are consistent.

[0098] The polarization curve test process of the half-cell of Comparative Example 1 is the same as that of Example 1.

[0099] Fig.14 This is a comparison of the polarization curves of the PCNCF prepared in Comparative Example 1 and the PCNCF-SN catalyst prepared in Example 1 in a half-cell; it can be seen that without the addition of 2,2'-bithiophene and pipemidic acid, the catalytic performance of PCNCF is seriously reduced, far inferior to PCNCF-SN, which shows that the introduction of 2,2'-bithiophene and pipemidic acid has a direct effect on the catalytic performance of the synthesized material. The above results show that the introduction of organic compounds containing non-metallic elements (S, N) in the present invention has a very important effect on the synthesis and catalytic performance of the material.

[0100] Comparative Example 2

[0101] This comparative example is intended to verify the different effects of introducing an S-containing organic compound raw material (2,2'-bithiophene) and a nitrogen-containing raw material (piperidic acid) on the synthesis and performance of the catalyst in the preparation method of the present invention.

[0102] The catalyst PtCuNiCoFe / CS (abbreviated as PCNCF-S) in this comparative example was prepared by the same steps as in Example 1, except that pipemidic acid was not added, and other conditions were the same as in Example 1.

[0103] Fig.15 is a comparison chart of X-ray diffraction of the catalysts prepared in Comparative Example 2, Comparative Example 1 and Example 1;

[0104] The polarization curve test process of the half-cell of Comparative Example 2 is the same as that of Example 1.

[0105] Fig.16 This is a comparison of the polarization curves of the PCNCF-S catalyst prepared in Comparative Example 3 and the PCNCF-SN catalyst prepared in Example 1 in a half-cell. Fig.14 It can be seen that compared with PCNCF without the introduction of S and N non-metallic sources, the introduction of S can enhance the anchoring effect of the carrier and significantly reduce the particle size;

[0106] from Fig.16It can be seen that the activity of the catalyst into which only S is introduced is far inferior to that of PCNCF-SN into which S and N are introduced together; from this comparative example, it can be seen that the introduction of the S element largely keeps the particle size small, while the introduction of the N element is very critical to high activity.

[0107] Comparative Example 3

[0108] This comparative example aims to verify that 2,2'-bithiophene as a ligand and sulfur source plays a key role in the successful preparation of the catalyst and the catalytic performance.

[0109] The three catalysts in this comparative example were prepared by the same steps as in Example 1 and were named PCNCF-piperidic acid, PCNCF-thiourea-piperidic acid and PCNCF-1,2-dimethylimidazole-piperidic acid, respectively, with the following differences: (1) 2,2'-bithiophene was not added; (2) thiourea was used instead of 2,2'-bithiophene; (3) 1,2-dimethylimidazole was used instead of 2,2'-bithiophene. Other conditions were the same as in Example 1.

[0110] Fig.17 The indigo curve is the X-ray diffraction pattern of PCNCF-piperidic acid prepared in the comparative example. It can be found from the figure that the peak shape of the diffraction peak is not symmetrical, which indicates that the PCNCF-piperidic acid catalyst prepared without 2,2'-bithiophene has segregation. In addition, the absence of ordered characteristic peaks indicates that PCNCF-piperidic acid is not a high entropy metal compound. The above results show that the ligand effect of 2,2'-bithiophene plays a key role in this synthesis method.

[0111] The polarization curve test process of the half-cell in Comparative Example 3 is the same as that in Example 1.

[0112] Fig.18 The green curve in the middle is the polarization curve of PCNCF-piperidic acid prepared in the comparative example in the half-cell; it can be seen from the figure that the catalytic performance of PCNCF-piperidic acid is much lower than that of PCNCF-SN in Example 1. The above results show that the use of 2,2'-bithiophene determines whether the high entropy metal compound can be successfully synthesized.

[0113] Fig.17 The purple curve in the figure is the X-ray diffraction pattern of the catalyst PCNCF-thiourea-piperidic acid prepared in the comparative example. It can be found from the figure that each diffraction peak of the material has obvious splitting, severe phase segregation exists, and no ordered diffraction peak appears, indicating that not every sulfur-containing ligand can play a role similar to 2,2'-bithiophene in the synthesis, and the thiourea ligand cannot effectively synthesize high entropy metal compounds. Fig.18The golden curve is the polarization curve of the catalyst PCNCF-thiourea-piperidic acid prepared in Example 2 in the half-cell. It can be seen from the figure that compared with PCNCF-SN in Example 1, the catalytic performance of PCNCF-thiourea-piperidic acid is much lower than that of PCNCF-SN. The above results show that the use of 2,2'-bithiophene and its ligand effect have a direct impact on the performance of the catalyst, and further prove that 2,2'-bithiophene as a ligand and sulfur source is closely related to the successful synthesis of high entropy metal compounds.

[0114] Fig.17 The red curve in the figure is the X-ray diffraction diagram of the catalyst PCNCF-1,2-dimethylimidazole-piperidic acid in this comparative example. It can be found from the figure that the catalyst has ordered diffraction peaks, indicating that high entropy metal compounds can be synthesized using nitrogen-containing ligands, but the diffraction peaks become abnormally sharp, indicating that the particle size of the synthesized catalyst increases sharply. It is known that the anchoring effect of N is not as good as that of S. This result further verifies the key role of 2,2'-bithiophene as a ligand and sulfur source in the synthesis. Fig.18 The blue curve in the figure is the polarization curve of the catalyst PCNCF-1,2 dimethylimidazole-piperidic acid in this comparative example in the half-cell; it can be seen from the figure that the catalytic performance of the high entropy metal intercompound PCNCF-1,2 dimethylimidazole-piperidic acid is much lower than that of PCNCF-SN in Example 1.

[0115] In summary, 2,2'-bithiophene plays a crucial role in the synthesis method of the present invention, which cannot be replaced by any sulfur-containing ligand, and its effect on the effective synthesis of high-entropy metal compounds is much greater than that of nitrogen-containing ligands. In addition, the catalytic performance of the high-entropy metal compound synthesized with 2,2'-bithiophene as a ligand and a sulfur source is better, which is mainly attributed to the stronger coordination effect of 2,2'-bithiophene, which better disperses the transition metal salt on the carbon carrier, and the anchoring effect brought by its doping as a S source on the carbon carrier, which further reduces the particle size of the catalyst and improves the activity and stability of the catalyst.

[0116] Comparative Example 4

[0117] This comparative example is intended to verify the key role of acetone as a solvent in the synthesis.

[0118] The catalyst in this comparative example was prepared by the same steps as in Example 1, and was named PCNCF-SN-methanol), except that methanol was used instead of acetone as the solvent, and the other conditions were the same as in Example 1.

[0119] Fig.17The blue curve in the figure is the X-ray diffraction pattern of the PCNCF-SN-methanol catalyst prepared in this comparative example. It can be found from the figure that the diffraction peak intensity of each crystal plane of the material is significantly reduced, and no ordered peak is observed, which indicates that methanol cannot be used as a solvent to synthesize high entropy metal compounds. This result further shows that acetone plays a key role as a solvent for the synthesis of effective high entropy metal compound materials.

[0120] The polarization curve test process of the half-cell in Comparative Example 4 is the same as that in Example 1.

[0121] Fig.18 The curve represented by the purple dotted line is the polarization curve of the PCNCF-SN-methanol catalyst prepared in this comparative example in the half-cell. It can be seen from the figure that compared with PCNCF-SN in Example 1, the performance of the PCNCF-SN-methanol catalyst is much lower than that of PCNCF-SN. The above results show that acetone as a solvent is directly related to whether the high entropy metal compound can be successfully synthesized.

[0122] Comparative Example 5

[0123] In order to further demonstrate the superiority of the PCNCF-SN catalyst material prepared in Example 1 in terms of synthesis process and performance, the parameters of the synthesis conditions and electrochemical properties of PCNCF-SN were compared with the high entropy metal intermetallic compounds synthesized by other methods reported in the current top magazines. As shown in Table 2, PCNCF-SN has excellent electrochemical properties as an oxygen reduction catalyst, and the synthesis method has the characteristics of simple steps, easy operation and low cost.

[0124] Table 3 Parameter comparison of the catalyst PCNCF-SN obtained in Example 1 and some high entropy intermetallic compound materials published in the past five years

[0125]

[0126] The literature:

[0127] (1)Wang, Y.; Gong, N.; Liu, H.; Ma, W.; Hippalgaonkar, K.; Liu, Z.; Huang, Y. Ordering-Dependent Hydrogen Evolution and Oxygen Reduction Electrocatalysis of High-Entropy Intermetallic Pt 4FeCoCuNi.Adv.Mater.2023,35(28),2302067.https: / / doi.org / 10.1002 / adma.202302067.

[0128] (2)Feng,G.;Ning,F.;Pan,Y.;Chen,T.;Song,J.;Wang,Y.;Zou,R.;Su,D.;Xia,D.Engineering Structurally Ordered High-Entropy Intermetallic Nanoparticleswith High-Activity Facets for Oxygen Reduction in Practical FuelCells.J.Am.Chem.Soc.2023,145(20),11140–11150.https: / / doi.org / 10.1021 / jacs.3c00868.

[0129] (3)Sulfur-anchoring synthesis of platinumintermetallic nanoparticlecatalysts for fuel cells|Science.https: / / www.science.org / doi / 10.1126 / science.abj9980(accessed 2023-10-29).

[0130] (4)Hu,Y.;Xu,Z.;Guo,X.;Xiong,P.;Xu,C.;Chen,C.;Zhang,Q.;Wang,S.;Wu,T.-S.;Soo,Y.-L.;Li,M.M.-J.;Wang,D.;Zhu,Y.Hollow-Carbon Confinement Annealing:ANew Synthetic Approach to Make High-Entropy Solid-Solution and IntermetallicNanoparticles.Nano Lett.2023,23(23),10765–10771.https: / / doi.org / 10.1021 / acs.nanolett.3c02882.

[0131] (5) Zhang, Q.; Shen, T.; Song, M.; Wang, S.; Zhang, J.; Huang, X.; Lu, S.; Wang, D. High-Entropy L12-Pt(FeCoNiCuZn)3Intermetallics for Ultrastable OxygenReduction Reaction.J. Chem.2023,86,158–166.https: / / doi.org / 10.1016 / j.jechem.2023.07.019.

[0132] (6)Chen, T.; Qiu, C.; Zhang, X.; Wang, H.; Song, J.; Zhang, K.; Yang, T.; Zuo, Y.; Yang, Y.; Gao, C.; Xiao, W.; Jiang, Z.; Wang, Y.; Xiang, Y.; OxygenReduction Reaction.J.Am.Chem.Soc.2024,146(1),1174–1184.https: / / doi.org / 10.1021 / jacs.3c12649.

[0133] By comparing the typical works in the past five years in Table 3, it can be found that the synthesis method of the present invention does not require pretreatment of the carbon carrier or construction of a special carbon carrier and template, and can directly use a commercial carbon carrier, which is very critical to the scale and commercialization of the method; at the same time, the particle size of the catalyst synthesized by the present invention is very small, which is very prominent compared with other methods, and can provide more catalytic active sites; it has high activity and excellent stability in oxygen reduction catalytic performance, and can still maintain more than 60% of its activity after 100,000 cycles.

[0134] In summary, the present invention overcomes the deficiencies in the prior art and provides a simple and convenient preparation method, by which a small nano-sized high entropy intermetallic compound co-doped with S and N is prepared, and the material exhibits excellent activity and excellent stability in the oxygen reduction reaction. In general, the present invention provides a new method for large-scale production of high-entropy intermetallic compound catalysts of high quality.

[0135] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a S, N co-doped small nano-sized high entropy intermetallic compound, characterized by: include, A noble metal salt and a transition metal salt, a sulfur source and a nitrogen source are added to an organic solvent, and the mixture is stirred at room temperature. A carbon carrier is added and stirred at room temperature to obtain a mixture, and the mixture is ultrasonically treated to form a uniform mixture A. The mixture A was stirred at room temperature, and the organic solvent was evaporated by heating to form a black viscous slurry B, which was transferred to a vacuum oven for drying to obtain an intermediate product; The intermediate product is subjected to high temperature annealing treatment in a reducing atmosphere to obtain a S, N co-doped small nano-sized high entropy intermetallic compound; Wherein, the sulfur source includes 2,2'-bithiophene, and the organic solvent includes acetone; The S, N co-doped small nano-sized high entropy intermetallic compound comprises a carbon carrier containing S and N co-doped heteroatom sites, metal single atom sites, and a high entropy intermetallic compound supported on a carbon substrate; The S, N co-doped small nano-sized high entropy intermetallic compound comprises high entropy intermetallic compound particles composed of more than 5 metal elements; The particle size of the S, N co-doped small nano-sized high entropy intermetallic compound particles is 2 to 5 nm.

2. The preparation method according to claim 1, characterized in that: The noble metal salt includes at least one of a platinum salt, an iridium salt, and a palladium salt; Among them, the platinum salt is platinum acetylacetonate, the iridium salt is iridium acetylacetonate, and the palladium salt is palladium acetylacetonate.

3. The preparation method according to claim 1 or 2, characterized in that: The transition metal salt is a combination of at least three of copper salt, nickel salt, cobalt salt, iron salt, manganese salt and chromium salt; Among them, the copper salt is copper acetylacetonate, the nickel salt is nickel acetylacetonate, the cobalt salt is cobalt acetylacetonate, the iron salt is iron acetylacetonate, the manganese salt is manganese acetylacetonate, and the chromium salt is chromium acetylacetonate.

4. The preparation method according to claim 3, characterized in that: The nitrogen source is any one of melamine, pipemidic acid, aminoantipyrine, triaminopyrazole and pyridine.

5. The preparation method according to claim 1 or 4, characterized in that: The carbon carrier is at least one of carbon black, carbon nanotubes and Ketjen black.

6. The preparation method according to claim 1, characterized in that: The molar ratio of the noble metal salt to the transition metal salt is (6-8):5; the mass ratio of the noble metal salt to the carbon carrier is (3-4):10; the mass ratio of the sulfur source, nitrogen source and carbon carrier is 1-2:1-2:1-12.

7. The preparation method according to claim 1 or 6, characterized in that: The step of adding a carbon carrier and stirring at room temperature to obtain a mixture, wherein the stirring time is 30 to 60 minutes; the step of ultrasonically treating the mixture to form a uniform mixture A, wherein the ultrasonic time is 1 to 4 hours; the step of heating and evaporating the organic solvent, wherein the temperature of the evaporating solvent is 70° C., and the action time is 0.5 to 1 hour; the step of transferring B to a vacuum oven for drying, wherein the drying temperature is 60° C., and the time is 12 to 24 hours.

8. The preparation method according to claim 1, characterized in that: The high temperature annealing atmosphere is 10% H2 / Ar, the annealing heating rate is 3-5°C / min, the annealing temperature is 800-1000°C, and the annealing time is 2-4h.

9. The S, N co-doped small nano-sized high entropy intermetallic compound obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the S, N co-doped small nano-sized high entropy intermetallic compound according to claim 9 in the cathode oxygen reduction reaction of a proton exchange membrane fuel cell.

Citation Information

Patent Citations

  • Non-metallic element doped multi-component platinum alloy carbon-supported catalyst and preparation method thereof

    CN114784305A

  • Supported high-entropy intermetallic compound catalyst, preparation method and application

    CN115360367A

  • Sulfur-doped metal nitrogen-carbon loaded low-platinum alloy composite catalyst and preparation method thereof

    CN115799542A

  • Interstitial non-metallic element doped high-entropy platinum alloy catalyst as well as preparation method and application thereof

    CN116666672A

Cited By

  • Platinum-based high-entropy intermetallic compound and preparation method thereof, and application of platinum-based high-entropy intermetallic compound as hydrogen fuel cell cathode catalyst

    CN120683390A

  • A platinum-based high-entropy intermetallic compound, a preparation method thereof and application thereof as a hydrogen fuel cell cathode catalyst

    CN120683390B

  • Ternary ordered alloy catalyst as well as preparation method and application thereof

    CN121172165A